Single‐Scan 13C Diffusion‐Ordered NMR Spectroscopy of DNP‐Hyperpolarised Substrates. Issue 66 (22nd September 2017) - Guduff, Ludmilla; Kurzbach, Dennis; van Heijenoort, Carine; Abergel, Daniel; Dumez, Jean‐Nicolas
Abstract: Diffusion‐ordered NMR spectroscopy (DOSY) is a powerful approach for the analysis of molecular mixtures, yet its application range is limited by the relatively low sensitivity of NMR. We show here that spectrally resolved 13 C DOSY data can be collected, in a single scan, for substrates hyperpolarised by dissolution dynamic nuclear polarisation (D‐DNP), which provides signal enhancements of several orders of magnitude. For this we use a convection‐compensation pulse scheme, which we also analyse by numerical simulation. The proposed method further allows the acquisition of several consecutive DOSY spectra in a single D‐DNP experiment. Abstract : Taken in one shot : 13 C DOSY NMR spectra are obtained in a single scan from DNP‐hyperpolarised substrates, using a convection‐compensated spatial encoding of the diffusion dimension.